O12 Safety and efficacy of EUS-FNA in HPB lesions- experience from non-HPB centre in UK. (19th June 2022) - Sethia, Rahul; Elzubier, Mohamed; Dasgupta, Kaushik; Hancock, John; Mitra, Vikramjit
Abstract : Introduction: EUS guided tissue acquisition is well established and extensively used investigation to confirm the histopathological diagnosis in PB lesions. The European Society of Gastrointestinal Endoscopy (ESGE) and Joint Advisory Group (JAG) suggests the frequency of obtaining a diagnostic tissue sample of at least 85% for EUS-FNA (1). The aim of this study was to determine the diagnostic yield, safety and efficacy of EUS-FNA in HPB lesions in a non-HPB centre in the UK. Methods: We carried out a retrospective audit of all patients (identified from endoscopy and pathology database) who underwent EUS guided tissue acquisition between 1st October 2019 and 30th November 2021. Data collected include patient demographics, cross-sectional imaging, cytopathological diagnoses (Panc 1 to 5 based on European cytopathology classification of Pancreatobiliary terminology), treatment modality, complications and 30-day procedure related mortality. Final diagnoses were confirmed from EUS biopsy, surgical resection specimen or cross-sectional imaging (discussed in a MDT setting if histology negative). Results: 130 patients [mean age 67.6 years, 43.8% females] underwent EUS-FNA procedures. 119 (91.5%) samples were deemed as adequate for analysis. Sensitivity, specificity, diagnostic accuracy, positive predictive value (PPV) and negative predictive value (NPV) were 88.5%, 100%, 86.9%, 100%, and 78.2% respectively [with Panc III included as false negative in patients with cancer as final diagnosis]. One patient, who had mild post procedure pancreatitis, was treated conservatively without hospital admission. There was no procedure related mortality. Histopathological diagnoses of cancer on EUS biopsy (n=77) – Adenocarcinoma (66), NET (6), Lymphoma (4), Squamous carcinoma (1) Conclusions: This study confirms that EUS-FNA of HPB lesions can be highly effective and safely carried out in a non-HPB centre. Overall adequacy of tissue acquisition is in compliance with ESGE & JAG guidelines. Our diagnostic yield is in in keeping with the published literature.